Effect of temperature and photoperiod on growth, development and reproduction of Nysius huttoni White (Heteroptera: Lygaeidae) : a thesis presented in partial fulfilment of the requirement for the degree of Master of Applied Science in Plant Protection at the Institute of Natural Resources, Massey University, Palmerston North, New Zealand - He, Xiongzhao (Massey University, 2000)
The influence of temperature, host plant and photoperiod on Nysius huttoni White growth, development and reproduction was investigated under laboratory conditions. The growth and development rate increased in linear fashion with temperature over the range of 15-30°C. The estimated lower temperature thresholds for all life stages were above 10°C except for the third instar on shepherd's purse (Capsella bursa-pastoris (L.) Medik.). Nysius huttoni completed its life cycle at 20, 25 and 30°C on twin cress (Coronopus didymus (L.) Sm.) and shepherd's purse, but could not develop through to the adult stage at 15°C on any of the test host plants or on chickweed (Stellaria media (L.) Vill.) at any of the test temperatures. Thermal requirement for completing the life cycle in N. huttoni was 625.00 degree-days on twin cress and 714.29 degree-days on shepherd's purse. The time needed for a life cycle of both sexes was similar but the adult longevity decreased as temperature increased. The estimated lower temperature thresholds for mating and oviposition on twin cress were 12.3°C 16.8°C, respectively. Females failed to lay eggs when both nymphs and adults were fed with shepherd's purse. Sunflower seed was conducive to sexual maturity and fecundity. The growth and development of N. huttoni slowed down as photoperiod decreased. Adults and fifth instar nymphs were sensitive to diapause-inducing photoperiod. When fifth instar nymphs and sequential adults were held at 12:12 and 10:14 h (L:D), 100% of females entered diapause. Females that had oviposition breaks over 50 days at 10:14 and 12:12 h (L:D) apparently entered diapause. However, exposure of the entire life cycle to 10:14 and 12:12 h (L:D) gave a significantly lower diapause incidence. The critical photoperiod for diapause was estimated between 13:11 to 13.5:10.5 h (L:D). Fecundity appeared to decrease with the decrease in photoperiod. The time needed for a life cycle and the longevity of both sexes were similar at a given photoperiod but increased as photoperiod decreased.
Keywords: Nysius huttoni -- Effect of temperature on; Nysius huttoni -- Effect of light on; Lygaeidae; Insects -- New Zealand